Improved PWM to Suppress Motor Overvoltage Caused by Voltage Reflection - Kim, Sung Oh; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2025)
This paper presents an improved PWM to suppress motor overvoltage caused by voltage reflection. The motor drive systems used in industry encounter overvoltage due to voltage reflection when long transmission lines are used. This overvoltage leads to motor damage, making its mitigation essential. One effective method for mitigating overvoltage is adjusting the PWM. The method of adjusting PWM dynamically controls the duty cycle to address the motor overvoltage by utilizing the oscillation frequency associated with motor overvoltage. The proposed method generates a new reference voltage using the new look-up table to suppress motor overvoltage even with adjusting the duty cycle. A flowchart of the proposed method is presented, considering its application to the controller. The validity of the proposed method is verified through simulations.
Keywords: Duty-cycle; Long transmission lines; Motor drive system; Motor overvoltage; Oscillation frequency; Over-voltages; Reference voltages; Transmission-line; Voltage reflection; Voltage waves; AC motor; motor overvoltage; transmission lines; voltage reflection; voltage wave